A double-blind, placebo-controlled, randomized, clinical trial of the TLR-3 agonist rintatolimod in severe cases of chronic fatigue syndrome. - David R Strayer; William A Carter; Bruce C Stouch; Staci R Stevens; Lucinda Bateman; Paul J Cimoch; Charles W Lapp; Daniel L Peterson; Chronic Fatigue Syndrome AMP-516 Study Group; William M Mitchell (PLoS ONE, 2012)
Chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is a severely debilitating disease of unknown pathogenesis consisting of a variety of symptoms including severe fatigue. The objective of the study was to examine the efficacy and safety of a TLR-3 agonist, rintatolimod (Poly I: C(12)U), in patients with debilitating CFS/ME.A Phase III prospective, double-blind, randomized, placebo-controlled trial comparing twice weekly IV rintatolimod versus placebo was conducted in 234 subjects with long-standing, debilitating CFS/ME at 12 sites. The primary endpoint was the intra-patient change from baseline at Week 40 in exercise tolerance (ET). Secondary endpoints included concomitant drug usage, the Karnofsky Performance Score (KPS), Activities of Daily Living (ADL), and Vitality Score (SF 36). Subjects receiving rintatolimod for 40 weeks improved intra-patient placebo-adjusted ET 21.3% (p = 0.047) from baseline in an intention-to-treat analysis. Correction for subjects with reduced dosing compliance increased placebo-adjusted ET improvement to 28% (p = 0.022). The improvement observed represents approximately twice the minimum considered medically significant by regulatory agencies. The rintatolimod cohort vs. placebo also reduced dependence on drugs commonly used by patients in an attempt to alleviate the symptoms of CFS/ME (p = 0.048). Placebo subjects crossed-over to receive rintatolimod demonstrated an intra-patient improvement in ET performance at 24 weeks of 39% (p = 0.04). Rintatolimod at 400 mg twice weekly was generally well-tolerated.Rintatolimod produced objective improvement in ET and a reduction in CFS/ME related concomitant medication usage as well as other secondary outcomes.ClinicalTrials.gov NCT00215800.